PENGARUH PILATES EXERCISE TERHADAP PENURUNAN SKALA NYERI DISMENORHEA PADA REMAJA PUTRI DI PURWOKERTO - Alvina Destyaningrum; Atun Raudotul Ma’rifah; Maria Paulina Irma Susanti (Universitas Harapan Bangsa Purwokerto, 2017)
Dismenorhea is pain that happen before or during menstruation. Dismenorhea can be mild is cramping pain in the genital area or something bad that can influence the daily activities. Symptoms that occurred in dismenorhea namely nausea and vomiting, diarrhea, headache, dizziness, sweating, tachycardia, and fainting. Nonfarmakology treatment that can be used to reduce pain of dismenorhea is doing pilates exercise. The purpose of this study was to determine the effect of Pilates exercise in reducing pain of scale dismenorhea in female teenagers in Orphanage Muhammadiyah Purwokerto. The type of this research is pre-experimental with the approach of one group pretest and posttest design. The technique sampling used was purposive sampling, where samples were taken in accordance with the will of the researcher. Respondents in this study were 18 people who suffered from dismenorhea. The data was taken by observing the pain scale before and after the pilates exercise using Numeric Rating Scale observation sheet. The statistical test used in this study was the Wilcoxon signed rank test. The results showed difference of dismenorhea pain scale before and after doing pilates exercise in adolescent girls in the orphanage Muhammadiyah Purwokerto, where the test results showed statistically significant value (0.00> 0.05). Thus, it was concluded that the pilates exercise can reduce pain scale dismenorhea in female teenagers in the Orphanage Muhammadiyah Purwokerto . Keywords: Pilates Exercise, Dismenorhea pain.